The secret annexe an anthology of the world's greatest war diaries - Taylor, Irene; Taylor, Alan F. (Canongate, 2004)
War infects everything it touches. For everyone, whether combatant or not, it is the most testing of times, when the old certainties and moral imperatives cannot be guaranteed. Life hangs by a gossamer thread and many people who would otherwise not keep diaries feel the need to record what they see, feel and do. Arranged like a diary, The Secret Annexe tells many individual stories - some horrific, some hilarious - of many wars down the ages, with several compelling entries for each day of the year. The diarists come from every walk of life, from friend and foe, from anonymous foot-soldiers to those charged with orchestrating battle, from the Home Front to the Holocaust, from famous writers, political leaders and fighting men and women to ordinary working people enveloped by events over which they have little influence. Together they contribute to the most intimate insight into what's been described as "the most exciting and dramatic thing in life". Complementing the diary entries are comprehensive biographies and bibliographies of the diarists as well as summaries of each of the wars covered.